Bencana dan Ketahanan Pangan Adaptasi Masyarakat Gumantar Ketika Terjadi Bencana - Uzlifatul Azmiyati (Mandala, 2019)
Geographically, geology, geomorphology, hydro-meteorology and socio-culture-economy Indonesia is a disaster-prone country. Almost every region in Indonesia is prone to disasters. Not only natural disasters such as earthquakes, tsunami, floods, landslides, droughts or tornadoes can occur, but also social disasters such as social conflicts, fires, disease outbreaks and technological failures. Disaster events have a significant impact on people's survival. Causing losses both morally and materially, including causing food security to be disrupted. When disasters, food availability can be reduced while the needs of post-disaster communities are increasing. Awareness of the importance of maintaining food security is one step in disaster mitigation activities. Good food management can help people recover faster after a disaster. This is what is done by Gumantar Village people in North Lombok Regency who have done food management well. The Gumantar community with rice barn, Pegawe Gumi, and mutual cooperation succeeded in passing through disasters that threatened food security. The granary structure that is the residence of Gumantar people makes them able to store food for a long time. Special rituals carried out for agriculture are also routinely carried out, namely Pegawe Gumi ritual. This good food management makes the Gumantar community able to survive after the Lombok earthquake 2018 or during a famine, without waiting for help from volunteers/donors. Adaptation of the Gumantar community through local wisdom that has always been maintained has increased their capacity in the face of disasters. Therefore, Gumantar community has been able to reduce the risk of disasters that might occur around them